2007
DOI: 10.1007/s10750-007-0599-4
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal dynamics of zooplankton in subtropical Lake Blanca (Uruguay) hosting multiple zooplankton predators and aquatic plant refuges

Abstract: In the subtropics, the effects of macrophytes on trophic interactions are more complex than in temperate lakes. Fish, particularly the smallest species and individuals, aggregate in high numbers in the vegetation, and a strong predation pressure on zooplankton by shrimps and invertebrates, such as Chaoborus, can occur in these systems. We studied seasonal and diel changes in zooplankton and their potential predators (both fish and invertebrates) and physical and chemical characteristics among open water and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
68
2
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 31 publications
13
68
2
6
Order By: Relevance
“…Very few works, however, have been studied the DHM in shallow lakes at tropical and subtropical regions (e.g. Meerhoff et al 2006, Iglesias et al 2007). According to Iglesias et al (2007), in the tropics and subtropics, the effects of the macrophytes on trophic interactions are more complex than in temperate lakes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few works, however, have been studied the DHM in shallow lakes at tropical and subtropical regions (e.g. Meerhoff et al 2006, Iglesias et al 2007). According to Iglesias et al (2007), in the tropics and subtropics, the effects of the macrophytes on trophic interactions are more complex than in temperate lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Meerhoff et al 2006, Iglesias et al 2007). According to Iglesias et al (2007), in the tropics and subtropics, the effects of the macrophytes on trophic interactions are more complex than in temperate lakes. In shallow subtropical lakes, the aquatic plants offer refuge to zooplankton only when fishes and invertebrate predators are not abundant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not only the abundance of different small water bodies in landscapes, but also the macrophyte mosaic within a single pond that will support as well as contribute to the increase of biological diversity. The presence of macrophyte species has a significant influence on the species richness and community structure (Balayla and Moss, 2003;Iglesias et al, 2007;Ejsmont-Karabin and Hutorowicz, 2011;Dalu et al, 2012). Additionally, the different plant habitats are fundamental for particular groups of zooplankton, creating various life conditions and anti-predator refuges of varying effectiveness (Stansfield et al, 1997;Balayla and Moss, 2003;Sˇpoljar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most research on small water bodies has concerned the summer season (To˜nno et al, 2003;Iglesias et al, 2007;Lucena-Moya and Duggan, 2011;McGavigan, 2012), when the majority of environmental factors, e.g., availability of a suitable food source or heterogeneity relating to the complexity of macrophyte cover, occur within optimum values. Hence, life conditions for inhabiting organisms are very advantageous at that time.…”
Section: Introductionmentioning
confidence: 99%
“…If predators are present among littoral vegetation and water quality outside the macrophyte stands is not favorable for visual @tion, prey animals may prefer the open water area instead of littoral vegetation zone even during daytime. Some studies have shown that in such situations zooplankton may show reversed DHM behavior, migrating from the vegetation zone to spend the daytime in the open water and returning to the littoral zone for the night (Numinen and Horppila 2002, Iglesias et al 2007). For fish, a common pattern of horizontal migration is movement away from the shordittoral zone at dusk or night to feed on abundant resources and returning to the shore at day (Bohl 1980, Gliwicz et al 2006 To clarify the habitat choice by small fish between a struct~ually complex refuge and a turbidity refuge, we conducted a study in the Kirkkojhi basin in southern Finland The lake is characterized by a very turbid open-water area that is surrounded by zones of floating-leaf and submersed vegetation where water turbidity is substantially reduced due to the reductive effect of macrophytes on sediment resuspension Nurminen 2003 and.…”
Section: Introductionmentioning
confidence: 99%